1995
DOI: 10.1021/j100038a002
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Relaxation in the Compressible Region of CO2: Evidence for Solute-Induced Clustering in Supercritical Fluid Solutions

Abstract: Rotational correlation times of two solutes, trans, trans-1 ,Cdiphenylbutadiene (DPB) and rrans-4-(hydroxymethy1)stilbene (HMS), have been measured in supercritical C02 as a function of density at a reduced temperature of 1.01 (35 "C) across the compressible region. The DPB rotational correlation time increases by 50% upon increasing density from 0.3 to 0.8 g/cm3, whereas the HMS rotational correlation time increases by more than 300% over the same density regime. The results are compared with a model that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 3 publications
10
68
3
Order By: Relevance
“…The local density enhancement in supercritical fluid has been thoroughly studied by theoretical and experimental means. 19,20,[41][42][43][44][45] In particular, Bai et al 43 determined the self-diffusion coefficients of methanol and 1-decanol in supercritical CO 2 by pulsed field-gradient NMR and concluded that a large local solvent density around the alcohol molecules under supercritical conditions will make the solute diffusion coefficient decrease. Similarly, the local density enhancement may be in part responsible for the observed decrease in mutual diffusion coefficients.…”
Section: Resultsmentioning
confidence: 99%
“…The local density enhancement in supercritical fluid has been thoroughly studied by theoretical and experimental means. 19,20,[41][42][43][44][45] In particular, Bai et al 43 determined the self-diffusion coefficients of methanol and 1-decanol in supercritical CO 2 by pulsed field-gradient NMR and concluded that a large local solvent density around the alcohol molecules under supercritical conditions will make the solute diffusion coefficient decrease. Similarly, the local density enhancement may be in part responsible for the observed decrease in mutual diffusion coefficients.…”
Section: Resultsmentioning
confidence: 99%
“…8 Such solvent-solute interactions may initiate CO 2 solvent clustering. 34 The spin-lattice relaxation time measurements were performed for this mixture in our laboratory, and the results are reported elsewhere. 22 Calculations of f stick and f slip for methanol are found to be 0.69 and 0.10, respectively, and the van der Waals volume is 41.8 Å 3 .…”
Section: Resultsmentioning
confidence: 99%
“…However, only a few such studies have been published with the goal of examining density augmentation in the compressible region of supercritical fluids. [3][4][5] In this paper we examine the rotational diffusion of two The lifetime spectrometer has been described in detail previously, [6] and the instrument response function is 50 psec. Rotational diffusion times are determined from the fluorescence lifetimes and fluorescence anisotropies using the Perrin equation.…”
Section: Rotationalmentioning
confidence: 99%